2005
DOI: 10.1111/j.1365-2036.2005.02333.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: oral ulcers and its relevance to systemic disorders

Abstract: Summary Oral ulceration is a common problem, and is sometimes a marker of gastroenterological disease. Patients with signs or symptoms of oral ulcers are sometimes referred to gastroenterology clinics, however, in most instances the ulcers does not reflect gastrointestinal disease. Indeed, a spectrum of disorders other than those of the gut can give rise to oral mucosal ulcers ranging from minor local trauma to significant local disease such as malignancy or systemic illness. This present article reviews aspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 78 publications
0
63
0
1
Order By: Relevance
“…At the end of the 12-day test period, the mean ulcer area of the Bnz HCl group was 31% smaller than that of the base and 33% smaller than that of the control groups. A similar patient study revealed no differences between Bnz HCl, chlorhexidine and placebo mouthwashes in the treatment of aphthous ulcers 14 , even though clinical benefits with benzydamine application have been previously reported 7,9,17,21 .…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…At the end of the 12-day test period, the mean ulcer area of the Bnz HCl group was 31% smaller than that of the base and 33% smaller than that of the control groups. A similar patient study revealed no differences between Bnz HCl, chlorhexidine and placebo mouthwashes in the treatment of aphthous ulcers 14 , even though clinical benefits with benzydamine application have been previously reported 7,9,17,21 .…”
Section: Discussionmentioning
confidence: 90%
“…Oral ulcers, an end-result of epithelial damage, may occur due to a number of causes including trauma 17,22 , immunemediated conditions such as aphthous stomatitis and lichen planus and lichenoid reactions 13,22 , cytotoxic therapy (such as radiation and chemotherapy) 8,9,24 , druginduced hypersensitivity reactions of the mucosa 22 and malignant changes 19 .…”
Section: Accepted For Publication 22 February 2011 Available Online 5mentioning
confidence: 99%
See 1 more Smart Citation
“…11 It has been shown that biochemical composition can also reflect the causes of some systemic disease. 12 Human saliva can reflect the relationship between oral hygiene and some chronic systemic diseases 13 as well as intensity of exercise. 14 …”
Section: Introductionmentioning
confidence: 99%
“…1 Most traumatic ulceration refl ects local physical aetiologies such as a broken tooth or dental restoration, or trauma from an orthodontic or prosthodontic appliance. Chemicals are a less common cause of traumatic ulceration.…”
Section: Introductionmentioning
confidence: 99%